Mini Research of Mandarin Oriental Singapore’s Commercial Text among New Students: A Commercial Material Development - Istiqomah, Lilik (Journal of English Teaching and Learning Issues, 2018)
This article mainly explores Mandarin Oriental Singapore’s Commercial Text among New Students: A Commercial Material Developments. This study uses participatory action research (PAR). The result indicates thatcommercial texts in the classroom student had autonomy in making a decision on particular lexico-grammatical resources they need to learn more or discuss with their pair, small group, and whole class discussion. They learn not only by locally produced materials but also commercial materials. These commercial materials drove them drawing on observation and reflective data, as the students engaged in meaning-making activities, they analyzed a variety of texts they read and shared the outcome of the analysis with their peers. This meaning-making engagement allowed them to understand and interpret texts in new and varied ways (Hodgson-Drysdale, 2014) so that relationship between content and language was evident.